Outcome of laparoscopic surgeries during pregnancy for non-obstetric emergencies - H. B., Sunitha; Bhat, Vidya V.; Bhat, Ravishankar; E., Nisha; Guddy, K. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was conducted to evaluate the surgical and obstetric outcome, safety and feasibility of various laparoscopic surgeries for non-obstetric indications in pregnancy. Methods: We did a retrospective analysis of 18 pregnant patients who underwent laparoscopic surgeries. Study period was from October 2013 till September 2015 conducted in Radhakrishna multispeciality hospital /IVF center Bangalore. Patients operated are 6 cases cholicystectomy, 6 cases appendicectomy, 5 adnexal mass removals, one salpingectomy for heterotopic pregnancy resulted from ART. All patients were between 11 to 32 weeks of gestation, with mean gestational age 21±6.5 weeks at the time of surgery and mean duration of surgery was 46±16.3 minutes. Results: All eighteen pregnant patients had uneventful hospital courses after laparoscopic procedures. Mean duration of hospital stay after surgery was 43±8.5 hours. One pregnancy was terminated at 11 weeks for suspected ovarian malignancy and 16 delivered full-term babies without complications, one patient delivered preterm at 35 weeks with NICU admission. The mean birth weight at the time of delivery was 2.8±550 gms. There was no maternal morbidity or mortality, or any identifiable neonatal birth defect. No conversion to laparotomy required in any case. Conclusions: Laparoscopic surgeries can be done in any trimester of pregnancy, but more safe and feasible during the second and early third trimester of pregnancy. Laparoscopic surgeries are as safe as laparotomy in the hands of experienced laparoscopic surgeon with no deleterious effects on either mother or fetus.